“My Goal Is to Lose 2.923 kg!”—Efficacy of Precise Versus Round Goals for Body Weight Reduction - Frech, Marie-Lena; Friese, Malte; Loschelder, David D. (Frontiers in Psychology, 2022)
Overweight individuals often struggle to lose weight. While previous studies established goal setting as an effective strategy for weight loss, little is known about the effects of numeric goal precision. The present research investigated whether and how the precision of weight loss goals—the number of trailing zeros—impacts a goal’s effectiveness. In two pre-registered, longitudinal experiments, we contrasted competing predictions as to whether precise (e.g., 2.923 kg) or round (e.g., 3.000 kg) goals are more effective compared to a waiting control condition. In Experiment 1 (N = 121), participants in the two goal conditions lost more weight compared to the control condition—an effect that was mainly driven by precise (rather than round) goals. In Experiment 2 (N = 150), we sought to replicate this effect but found no significant weight loss differences. An individual-participant data (IPD) meta-analysis across both experiments revealed that (a) the goal groups jointly lost more weight than the waiting control group, and (b) the precise and round goal groups did not differ in weight loss success. An IPD-based multiple mediation analysis showed that healthier eating, but not physical exercise accounted for goal-setting-induced weight loss. We discuss possible explanations for the null-findings in Experiment 2 and highlight directions for future research.